Let's solve the equation step by step and fill in the blanks correctly.
Starting with the equation:
\[ -3x - 9 = -21 \]
The first step is to add 9 to both sides:
\[ -3x - 9 + 9 = -21 + 9 \]
This simplifies to:
\[ -3x = -12 \]
Now we divide both sides by -3:
\[ x = \frac{-12}{-3} \]
This simplifies to:
\[ x = 4 \]
Now filling in the blanks:
-
The equation should read as \(-3x - 9 = \underline{-12}\).
-
The step "Add 9 to both sides" results in \(-3x = \underline{-12}\).
-
The division gives us \(x = \underline{4}\).
So the final filled in sentences will be:
-3x - 9 = -12
-3x = -12 (Add 9 to both sides) x = 4 (Divide both sides by -3)